HUBUNGAN KEPATUHAN MINUM OBAT DAN EFEKTIFITAS PENGOBATAN MELALUI NILAI HbA1C PADA PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS SEGIRI KOTA SAMARINDA - Wandilla, Intan; Juliyanti, Juliyanti; Anwar, Alfin (Journal of Sustainable Transformation, 2025)
Diabetes mellitus (DM) is caused by blood sugar levels exceeding normal values. If DM is not treated properly, it can cause various complications, thus endangering. This study aimed to determine the relation between medication adherence and treatment effectiveness through HbA1C values, in patients with diabetes mellitus at the Segiri Community Health Centre. The research method employed a quantitative approach with cross-sectional observations. The search sample used primary data in the form of a questionnaire distributed to diabetes mellitus patients at the Segiri Community Health Centre. Data analysis was descriptive using SPSS 23.0. The data analysis technique is the Chi-square test. The research results showed that 14 (25,5%) respondents had a compliance level of “Compliant”, 19 (34,5%) respondents had a compliance level of “Medium”, and 22 (40%) respondents had a compliance level of “Not Compliant”. Based on data from research conducted at the Segiri Community Health Center, there were 14 patients (56%) with HbA1C values <7%. These results show that treatment carried out for 8-14 weeks has quite good effectiveness.